Use of low-intensity laser radiation in sports activity of boxers - Melnikov, D. S.; Shchedrina, Yu. A. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to identify changes in the regulation of the heart rhythm in highly skilled boxers in the preparatory period against the background of the potentiating effect of low-intensity laser radiation (LILR).